2014
DOI: 10.1186/1550-2783-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Deep mineral water accelerates recovery after dehydrating aerobic exercise: a randomized, double-blind, placebo-controlled crossover study

Abstract: BackgroundThe effect of deep mineral water (DMW) with moderate mineralization on the recovery of physical performance after prolonged dehydrating aerobic exercise in the heat was studied in nine healthy, physically active (VO2max = 45.8 ± 8.4 mL kg−1 min−1) women aged 24.0 ± 3.7 years.MethodsWe conducted a randomized, double-blind, placebo-controlled crossover human study to evaluate the effect of ingestion of natural mineral water extracted from a depth of 689 m on recovery from prolonged fatiguing aerobic ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
4
21
0
Order By: Relevance
“…A proof-of-concept study has previously reported a substantially faster recovery (shortened from 48 to 4 h) on both leg muscle power (on a force plate) and aerobic fitness (maximal aerobic power on a cycle ergometer) in men stressed by an initial bout of exercise at high temperature (cycling at ~30°C until a 3% weight loss) with DOM supplementation (Hou et al, 2013 ). Similar results have been shown elsewhere, using different sources of mineral water from depths lower than 0.5 km below the earth's surface (Stasiule et al, 2014 ; Fan et al, 2016 ; Keen et al, 2016 ).…”
Section: Introductionsupporting
confidence: 89%
“…A proof-of-concept study has previously reported a substantially faster recovery (shortened from 48 to 4 h) on both leg muscle power (on a force plate) and aerobic fitness (maximal aerobic power on a cycle ergometer) in men stressed by an initial bout of exercise at high temperature (cycling at ~30°C until a 3% weight loss) with DOM supplementation (Hou et al, 2013 ). Similar results have been shown elsewhere, using different sources of mineral water from depths lower than 0.5 km below the earth's surface (Stasiule et al, 2014 ; Fan et al, 2016 ; Keen et al, 2016 ).…”
Section: Introductionsupporting
confidence: 89%
“…We have previously found an accelerated recovery from muscle fatigue in men consuming DOM drink during recovery after a prolonged exercise ( Hou et al, 2013 ). Similar studies using different sources of mineral water collected from depths lower than 0.5 km below the earth’s surface have demonstrated consistent results in improved muscle fatigue against an exercise challenge ( Stasiule et al, 2014 ; Fan et al, 2016 ; Keen et al, 2016 ). The underlying mechanism to explain the significant outcomes on muscle recovery remains unclear.…”
Section: Introductionmentioning
confidence: 53%
“…Findings from this study indicate that food plays an important role in mediating fluid recovery following exercise when beverages with basic nutrient profiles are consumed. Although the present investigation did not incorporate a "beverage only" trial for direct comparisons, the available evidence suggests that if food is not consumed, just ~30-56% of water (Maughan and Leiper 1995;Shirreffs and Maughan 1998;Shirreffs et al 2007a;Shirreffs et al 2007b;Merson et al 2008;Wong and Chen 2011;James et al 2014;Stasiule et al 2014;Tai et al 2014;Wong et al 2014;Seery and Jakeman 2016) and ~38-64% of sports drink (Wong et al 2000;Shirreffs et al 2007a;Shirreffs et al 2007b;Watson et al 2008;Evans et al 2009b;James et al 2011;Wong and Chen 2011;James et al 2012;James et al 2013;Clayton et al 2014;Desbrow et al 2014;Tai et al 2014;Wong et al 2014;Li et al 2015;Seery and Jakeman 2016) is typically retained post-ingestion (1.50 L•kg BM lost -1 ). Values indicated in the current investigation are noticeably higher (Water: 70.2±13.6%; Sports Drink: 74.2±18.1%).…”
Section: Discussionmentioning
confidence: 93%